IMPLIKATUR PERCAKAPAN DALAM NOVEL “SEORANG LAKI-LAKI YANG KELUAR DARI RUMAH” KARYA PHUTUT EA: CONVERSATIONAL IMPLICATURE IN THE NOVEL ‘SEORANG LELAKI YANG KELUAR DARI RUMAH’ BY PHUTUT EA - Tupong, Indra S.; Salam; Asri, Aswati (Journal of Applied Linguistics and Literature, 2025)
This research aims to describe the use of conversational implicatures in the novel "A Man Who Leaves the House" by Phutut EA. Type of descriptive qualitative research. The data source is the speech of the characters in the novel. Data collection techniques in this research are reading techniques and note-taking techniques. The research results revealed that there were 5 general conversational implicatures, 5 specific conversational implicatures, and 10 themed conversational implicatures in the novel "Seorang Laki-laki yang Keluar dari Rumah" by Phutut EA.